2014
DOI: 10.1038/nature12903
|View full text |Cite
|
Sign up to set email alerts
|

Broadly permissive intestinal chromatin underlies lateral inhibition and cell plasticity

Abstract: Cells differentiate when transcription factors (TFs) bind accessible cis-regulatory elements to establish specific gene expression programs. In differentiating embryonic stem (ES) cells, chromatin at lineage-restricted genes becomes sequentially accessible1-4, probably by virtue of “pioneer” TF activity5, but tissues may utilize other strategies in vivo. Lateral inhibition is a pervasive process in which one cell forces a different identity on its neighbors6, and it is unclear how chromatin in equipotent proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
233
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(249 citation statements)
references
References 41 publications
14
233
2
Order By: Relevance
“…This context-independent binding to cognate E-boxes has also been shown for the Drosophila Atonal protein (24). Despite this, the Atoh1 binding sites found in intestinal secretory cells show only a small overlap with those found in cerebellum granule neurons (951 out of 8729 detected in the gut) (23). So far, there are no data on Atoh1 binding sites in hair cells or dorsal interneurons: Atoh1 ChIP-seq experiments are problematic due to the very small numbers of these cell types (25,26 (27).…”
Section: Context Dependence Of Atoh1supporting
confidence: 52%
See 2 more Smart Citations
“…This context-independent binding to cognate E-boxes has also been shown for the Drosophila Atonal protein (24). Despite this, the Atoh1 binding sites found in intestinal secretory cells show only a small overlap with those found in cerebellum granule neurons (951 out of 8729 detected in the gut) (23). So far, there are no data on Atoh1 binding sites in hair cells or dorsal interneurons: Atoh1 ChIP-seq experiments are problematic due to the very small numbers of these cell types (25,26 (27).…”
Section: Context Dependence Of Atoh1supporting
confidence: 52%
“…The idea that Atoh1 regulates distinct targets in different cell types has been borne out in recent studies that have employed ChIP-seq to determine Atoh1 binding sites in cerebellum granule neurons (22) and intestinal secretory cells (23). Both studies identified a similar Atoh1 DNA binding motif (brain: (G/A)(C/A)CA(G/T)(C/A)TG(G/T)(C/T) and intestine: CA(G/C)CTG(G/T)(C/T)) indicating that differences in cellular context do not appear to strongly affect Atoh1 preference for its unique E-box motif (Fig.…”
Section: Context Dependence Of Atoh1mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether altered Tgfβ signaling had gene expression enrichment for secretory precursor cell genes, we again started by using GSEA (32) and comparing secretory progenitors with enterocytes (34). GSEA on the microarray data showed that the Tgfβ inhibitor resulted in decreased expression of genes characteristic of secretory precursor cells, whereas Tgfβ ligand treatment showed increased expression of the same genes (Fig.…”
Section: Cultured Intestinal Enteroids Reveal a Role For Tgfβ Signalimentioning
confidence: 99%
“…The power of the microenvironment on cell plasticity, apart from cellintrinsic mechanisms, has been detected as well during normal homeostatic lineage differentiation of untransformed intestinal stem cells (ISM), demonstrating that epithelial lineage separation is reversible and therefore not a true lineage commitment. Kim et al [63] showed that ISC are equipotent, and lineage differentiation from ISC does not require differential chromatin priming, as progenitors for different lineages display comparable histone modifications and chromatin access regions, and are rather dependent on environmental stimuli and rely on transcription factor activity (Atoh1) for determining the fate of stem cells or the reversion of differentiated cells into ISM.…”
Section: Inflammatory Microenvironment: Inflammatory Mediators Inducementioning
confidence: 99%